PREMIUM PRICE PENGELOLAAN SUMBERDAYA HUTAN PRODUKSI BERSERTIFIKASI - Rina Muhayah Noor Pitri (EnviroScienteae, 2016)
Forest certification is a key issue in relation to the forest products industry. It's also a new trend market of forest products. Forest certification is a guarantee that the products resulting from the forest management process in accordance with the standard of sustainable forest resources management. Certification will be increasing the cost of management as an impact of fulfilling requirement on the criteria of the certified forest. The fundamental question whether the award of certified products has been accompanied by an increase in premium price for forest estate or only becoming as the cost that reducing profit for the forest estate. The aims of this research are: 1) to know the difference between the sales price of certified and non-certified wood, 2) to know the premium price on certified forests, 3) to identify the factors that influence the amount of premium price of the certified forest. Data collection were used by searching the document and literature reference on forest certification. The results showed that the premium price received from the certified timber is higher than non-certified timber. Certified wood with high quality has a premium price that is greater than the low-quality wood. The percentage of premium price received varied forest estate. Premium price sometimes unsignificantly received by small-scale of timber estate. The revenue of premium price of certifies forest is influenced by the following factors: 1) The forest area to be certified, 2) Organizations that perform assessments, 3) Company / bodies / organizations that filed the certification, 4) he The country as a buyer of certified timber product 5) the facilitator in the market activities, 6) post-certification fee, and 7) the sales price.